Clinical Experience with the New EASY (Endoscopic Approach to the Symphysis) Preparation Technique for Injuries of the Anterior Pelvic Ring - Küper, Markus Alexander; Stöckle, Ulrich; Stuby, Fabian; Trulson, Alexander (Zeitschrift für Orthopädie und Unfallchirurgie, 2022)
Background High-energy injuries of the anterior pelvic ring and especially disruptions of the pubic symphysis usually require surgical stabilization. There is a conflict between biomechanical stability and size in the surgical approach. We have previously presented a minimally invasive approach for symphyseal plating.Methods Our current endoscopic surgical technique is presented step-by-step and is illustrated in a video. The results and courses of the first seven patients treated with the EASY preparation are presented.Results In all seven patients, the EASY preparation was successful. In four of the seven patients with an anterior pelvic ring injury, we performed a complete endoscopic plate osteosynthesis of the pubic symphysis. One patient gave consent only for endoscopic preparation, in one patient, we converted to open plate due to ventilation problems, and in one patient, the superior pubic rami fracture was stable. There were no surgical complications.Conclusion The EASY is a feasible minimally invasive preparation technique to stabilize anterior pelvic ring injuries in the most biomechanically stable manner by performing plate osteosynthesis. However, further scientific monitoring is necessary to improve the technique and validate our data.
Keywords: Symphysensprengung; Beckenringfraktur; Endoskopie; Laparoskopie; Open-book-Verletzung